A Case of Somatoform Disorder Due to COVID-19 Induced Trauma (Central Asian Journal of Medical Sciences, 2021)
Objectives: The COVID-19 pandemic has led to mental health problems, such as phobia, anxiety, insomnia, and depression. We report the case of somatoform disorder due to psychological trauma associated with COVID-19 disease. Method: Diagnosis was based on mental state examination and the patho-psychological testing. Results: A 70 years old female presented many somatic complaints. She had 12 visits to a specialist during more than 4 months, 4 hospital admissions, and was involved in many tests and treatments, but with no beneficial results. On mental state examination and patho-psychological testing were found anxiety, depression, and somatization. Conclusion: On the basis of clinical features, the patient was hospitalized and effectively treated with a combination of antidepressant, anxiolytics, psychotropics, and psychotherapy.